2012
DOI: 10.1134/s1234567812040015
|View full text |Cite
|
Sign up to set email alerts
|

Типы Гинецея Покрытосеменных Растений: Терминология И Проблемы Интерпретации, "Ботанический Журнал"

Abstract: При описании морфогенеза гинецея необходимо учитывать следующие базовые характеристики: 1) основным элементом гинецея является такой вариант, на базе которого формируется плод, подобный листовке; 2) морфологической базой сутуральной плацентации является U-образная плацента, включающая центральную плаценту в основании плодолистика и латеральные плаценты в области объединения его вентральных краев; 3) организация гинецея изменяется в ходе морфогенеза и его строение перед опылением создается на неодинаковой основ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Floral vascularization in all investigated species is quite simple and corresponds to those reported previously for Gagea by Joshi (1940) and Shamrov (2010Shamrov ( , 2012. e only important thing to note here is that placentas are supplied not only by ventral bundles, but also by lateral bundles.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Floral vascularization in all investigated species is quite simple and corresponds to those reported previously for Gagea by Joshi (1940) and Shamrov (2010Shamrov ( , 2012. e only important thing to note here is that placentas are supplied not only by ventral bundles, but also by lateral bundles.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, it is crucial to reconstruct the primary structure of the gynoecium and determine its secondary transformations. Shamrov (2010Shamrov ( , 2012 investigated the vertical zonality of the gynoecium in G. stipitata Merckl. ex Bunge [= G. kunawurensis (Royle) Greuter] and found that it consisted of syncarpous, paracarpous, and apocarpous zones following the terminology of Tahtadzhjan (1980).…”
Section: Discussionmentioning
confidence: 99%